Estimation of [177Lu]PSMA-617 tumor uptake based on voxel-wise 3D Monte Carlo tumor dosimetry in patients with metastasized castration resistant prostate cancer - Götz, Theresa Ida; Lang, Elmar Wolfgang; Prante, Olaf; Cordes, Michael; Kuwert, Torsten; Ritt, Philipp; Ludwig, Bernd; Schmidkonz, Christian (Nuklearmedizin-Nuclear Medicine, 2020)
Objective Patients with advanced prostate cancer are suitable candidates for [ 177Lu]PSMA-617 therapy. Integrated SPECT/CT systems have the potential to improve the accuracy of patient-specific tumor dosimetry. We present a novel patient-specific Monte Carlo based voxel-wise dosimetry approach to determine organ and total tumor doses (TTD). Methods 13 patients with histologically confirmed metastasized castration-resistant prostate cancer were treated with a total of 18 cycles of [ 177Lu]PSMA-617 therapy. In each patient, dosimetry was performed after the first cycle of [ 177Lu]PSMA-617 therapy. Regions of interest were defined manually on the SPECT/CT images for the kidneys, spleen and all 295 PSMA-positive tumor lesions in the field of view. The absorbed dose to normal organs and to all tumor lesions were calculated by a three dimensional dosimetry method based on Monte Carlo Simulations. Results The average dose values yielded the following results: 2.59 ± 0.63 Gy (1.67-3.92 Gy) for the kidneys, 0.79 ± 0.46 Gy (0.31-1.90 Gy) for the spleen and 11.00 ± 11.97 Gy (1.28-49.10 Gy) for all tracer-positive tumor lesions. A trend towards higher TTD was observed in patients with Gleason Scores > 8 compared to Gleason Scores ≤ 8 and in lymph node metastases compared to bone metastases. A significant correlation was determined between the serum-PSA level before RLT and the TTD (r = -0.57, p < 0.05), as well as between the TTD with the percentage change of serum-PSA levels before and after therapy was observed (r = -0.57, p < 0.05). Patients with higher total tumor volumes of PSMA-positive lesions demonstrated significantly lower kidney average dose values (r = -0.58, p < 0.05). Conclusion The presented novel Monte Carlo based voxel-wise dosimetry calculates a patient specific whole-body dose distribution, thus taking into account individual anatomies and tissue compositions showing promising results for the estimation of radiation doses of normal organs and PSMA-positive tumor lesions.
CRIS-Team Scopus Importer:2020-07-31
Keywords: dosimetry; prostate cancer; PSMA; radioligand therapy